Recent Advances in Halide Perovskite Single‐Crystal Thin Films: Fabrication Methods and Optoelectronic Applications (Solar RRL 4∕2019). Issue 4 (8th April 2019) - Wang, Xu‐Dong; Li, Wen‐Guang; Liao, Jin‐Feng; Kuang, Dai‐Bin
Abstract : Halide perovskite single crystal films that inherit the distinct properties of both bulk single crystal and polycrystalline film such as low trap density, high carrier mobility, and well‐defined thickness have aroused widespread attention. In article no.1800294, Dai‐Bin Kuang and co‐workers review recent progresses in the fabrication methodologies, physical and chemical properties, as well as the optoelectronic applications of perovskite single crystal thin films.